A compact model of organic thin-film transistors for display device. (June 2017) - Lu, Jiang Nan; Li, Hong Ge
Abstract: Organic transistor has been widely studied for next generation flexible semiconductor process. In this paper, we proposed the organic thin-film transistors (OTFT) model for the display device at the moderately high temperature (above 273 K). The model based on hopping theory of Gaussian disordered density-of-states (DOS) considers the dependences relationship of the carrier mobility with temperature and carrier concentrations. Charge transport is controlled by carrier jumps from trap states around the Fermi level to tail trap states at large carrier concentrations. The sub-threshold model is modified using an exponential function to make the model cover all regimes of OTFT operation. A pentacene-based thin film transistor (TFT) model has been designed using Verilog-A language. The model has been verified by device simulations and measurements.